Fibronectin extra domain A stabilises atherosclerotic plaques in apolipoprotein E and in LDL-receptor-deficient mice - Pulakazhi Venu, V.; Uboldi, P.; Dhyani, A.; Patrini, A.; Baetta, R.; Ferri, N.; Corsini, A.; Muro, A.; Catapano, A.; Norata, Giuseppe (2015)
© Schattauer 2015. The primary transcript of fibronectin undergoes alternative splicing in the cassette-type EDA and EDB exons and in the IIICs segment to generate different protein isoforms. Human carotid atherosclerotic plaques with a more stable phenotype are enriched with EDA containing fibronectin (FN-EDA). The aim of this study was to investigate the role of EDA containing fibronectin during atherogenesis. Mice constitutively expressing or lacking the EDA domain of fibronectin (EDA +/+ or EDA -/- ) were crossed with ApoE -/- or LDL-R -/- mice and fed with a western type diet for 12 weeks. Lack of FN-EDA resulted in reduced atherosclerosis and in a plaque phenotype characterised by decreased calponin positive VSMC’s (-15 %) and increased macrophages (+20 %). This was paralleled by increased MMP2, MMP9, and reduced TIMP2, collagen 1A1, 1A2 and 3A1 gene expression compared to that of wild-type and EDA +/+ mice. In vitro, VSMCs and macrophages isolated from EDA -/- mice showed increased MMPs expression and activity compared to wild-type or EDA +/+ mice. Albumin-Cre recombinase/ EDA +/+ /ApoE -/- mice, which produce EDA containing FN only in peripheral tissues, presented an extension, a composition and a gene expression pattern in the atherosclerotic lesions similar to that of controls. The inclusion of EDA in FN results in larger atherosclerotic plaques compared to mice lacking EDA but with a more favourable phenotype in two animals models of atherosclerosis. This effect depends on the EDA-containing fibronectin produced by cells in the vasculature but not in the liver. These observations set the stage for investigating the properties of circulating EDA containing FN in improving plaque stability.